Integration of Quantum Philosophy and Islamic Spirituality in Tawhid Based Education - Rachanda Ambya; Yusuf Sugiana; Tatang Muh Nasir; Erni Haryanti (STAI Hubbulwathan Duri, 2025)
This study explores the potential of quantum philosophy as a conceptual bridge between Islamic spirituality and modern scientific understanding, with implications for developing monotheism-based Islamic education. While quantum physics emphasizes empirical measurement and mathematical precision, quantum philosophy engages with the interpretative and metaphysical meanings of quantum phenomena. Key principles such as quantum entanglement, the uncertainty principle, and superposition are examined for their philosophical alignment with core Islamic concepts including tawhid (divine unity), tawakkal (trust in God), and multidimensional spiritual existence. Employing a qualitative, literature-based methodology, this research synthesizes perspectives from quantum theory, Islamic theology, and educational philosophy to construct an integrative framework. Sources were selected for their relevance to both quantum theory and Islamic educational discourse. The findings reveal meaningful analogies: quantum entanglement reflects the interconnectedness of all creation under divine will; the uncertainty principle parallels the Islamic notion of human limitation and trust in God; and superposition aligns with the layered nature of human existence—spiritual, moral, and material. The discussion highlights how these analogies can be incorporated into curriculum design, teaching strategies, and assessment tools within Islamic educational settings. The integration fosters a holistic learning paradigm that harmonizes scientific reasoning with faith-based values, encouraging critical thinking, ethical development, and spiritual consciousness. In conclusion, this study presents a theoretical model that supports the integration of quantum concepts into Islamic pedagogy, offering a foundation for future empirical research and curriculum innovation that reflects the unity of knowledge in Islamic epistemology.